IMPACT OF CUSTOMER BEHAVIOR AND SHORT VIDEO MARKETING ON CHINESE CUSTOMER LOYALTY TO ETHNIC MINORITY CLOTHING - Zhou, Zijing; Run, Pharatt (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to investigate the impact of customer behavior and short video marketing on the loyalty of Chinese consumers toward ethnic minority clothing. A total of 407 responses were collected from Chinese consumers who had purchased ethnic minority clothing through short video marketing platforms. The data was gathered from Kunming, Honghe, and Xishuangbanna. The statistics used to analyze the data were descriptive statistics, including frequency, percentage, mean, standard deviation, and standard deviation, and inferential statistics, including independent samples t-test, one-way ANOVA, LSD, and multiple linear regression with a statistical significance level of 0.05. The results found that the most representative age group is 25-34. The majority of respondents are from the Dai ethnic group. They are from Honghe. In terms of gender, the majority are female. Regarding occupation, the proportion of freelancers among the respondents is the highest. The education level of the respondents is relatively high, with the majority having received higher education. In terms of income, the middle-income group (4000-6000 per month) constitutes the largest portion of the sample. The first hypothesis was tested, and it was found that occupation significantly impacted customer loyalty. The second hypothesis was tested, and it was found that customer behavior did not generate the difference in customer loyalty based on various customer behavior factors such as buying time, way to buy, times per month, payment method, video marketing app, reasons for care, and reasons for buy. The third hypothesis was tested, and it was found that Short video marketings impact customer loyalty to ethnic minority clothing.